2015
DOI: 10.1155/2015/213583
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior of Concrete Beams Reinforced with GFRP Shear Reinforcement

Abstract: This paper presents the shear capacities of concrete beams reinforced with glass fiber reinforced polymer (GFRP) plates as shear reinforcement. To examine the shear performance, we manufactured and tested a total of eight specimens. Test variables included the GFRP strip-width-to-spacing ratio and type of opening array. The specimen with a GFRP plate with a3×2opening array showed the highest shear strength. From the test results, the shear strength increased as the strip-width-to-strip-spacing ratio increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In Figure 8 , the GFRP width of component and spacing are defined. The accuracy of equation (4) was verified by earlier researchers 6,7 . where, V sL is the nominal shear strength provided by longitudinal shear reinforcement, A f is sectional area of a vertical component of GFRP shear reinforcement, f fu is tensile strength of GFRP shear reinforcement, t f is thickness of GFRP shear reinforcement, w f is width of shear reinforcement, and s is center-to-center spacing of longitudinal shear reinforcement.…”
Section: Proposed Shear Strength Equaitonsupporting
confidence: 55%
See 1 more Smart Citation
“…In Figure 8 , the GFRP width of component and spacing are defined. The accuracy of equation (4) was verified by earlier researchers 6,7 . where, V sL is the nominal shear strength provided by longitudinal shear reinforcement, A f is sectional area of a vertical component of GFRP shear reinforcement, f fu is tensile strength of GFRP shear reinforcement, t f is thickness of GFRP shear reinforcement, w f is width of shear reinforcement, and s is center-to-center spacing of longitudinal shear reinforcement.…”
Section: Proposed Shear Strength Equaitonsupporting
confidence: 55%
“…The tensile stress of the GFRP plate was 480 MPa. The GFRP plates were manufactured as shown Figure 1 6,7 .…”
Section: Experimental Programmentioning
confidence: 99%
“…(1) ACI 440.1R [14] provides a shear strength equation for concrete with FRP flexural reinforcement. However, Kim et al [15] verified that in the case of a specimen reinforced by a plate type, substituting the tensile strength for the shear strength in the equation in ACI 318-14 is more reasonable than using the equation described in ACI 440.1R. In this paper, when considering plate type and stirrups as shear reinforcement nominal shear strength is calculated using the equation in ACI 318-14 and Kim et al, as shown in Equations (1)-(4).…”
Section: Lubell's Equation For Support Conditionsmentioning
confidence: 97%
“…Previous studies [33][34][35][36][37][38][39] have shown that the shear span-to-depth ratio significantly affects the shear behaviour of RC elements. However, this term has been ignored in current design code equations [40,41], which estimate the shear capacity of RC beams.…”
Section: Shear Span-to-depth Ratio 411 Control Beam Specimensmentioning
confidence: 99%